In situ transmission electron microscopy deformation and mechanical responses of additively manufactured Ni-based superalloy. (September 2020) - Guo, Qianying; Kirka, Michael; Lin, Lianshan; Shin, Dongwon; Peng, Jian; Unocic, Kinga A.
Abstract: In situ nanodeformation by sharp indenter tip on nanopillars of various sizes was applied on an additively manufactured Ni-based alloy containing equiaxed grains and nano-features for the first time. In situ microscopy compression results showed more homogeneous deformation of the smaller nanopillars (compression mode) than the larger ones (indentation mode) due to their length and the contact area between the nanopillar and the indenter tip established during in situ deformation tests. Finite element modeling indicated a higher average stress level in smaller nanopillars. The local mechanical response of additively manufactured 718 was similar to a wrought 718 alloy. Graphical abstract: Image, graphical abstract